Membentuk Peserta Didik Meneladani Yesus yang Inklusif - Hisardo Sitorus; Desy H. Sihombing; Rahel Dwi Ivanna; Yuki Tambunan (Jurnal Pendidikan dan Sastra Inggris, 2025)
The diversity of society necessitates a learning process that respects each individual as God's creation and equal before God, making the study of inclusive education from a Christian perspective vital. the need to develop pupils who follow Jesus example of inclusivity in order to develop into people who can love, accept, and embrace everyone regardless of differences. This study intends to define the significance of Jesus inclusive example, clarify its applicability to Christian religious education, and develop useful tactics for teachers to help create inclusive learners. The study combines a library research methodology with a qualitative method. review of the literature on the subject of Christian Religious Education instructors, inclusive education, and inclusive theology. According to the study’s findings, the fundamental tenets of successful inclusive education are love, acceptance, empathy, and respect for diversity. Students character could be shaped to be more responsible, compassionate, and open by putting these ideals into practice. Today's educators, parents, and churches would greatly benefit from guidelines for creating love-based learning that is suitable for the needs of students in a variety of settings.